2018
DOI: 10.1186/s12916-018-1136-1
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study examining how nano-liquid chromatography–mass spectrometry and phosphoproteomics can differentiate patients with advanced fibrosis and higher percentage collagen in non-alcoholic fatty liver disease

Abstract: BackgroundNon-alcoholic steatohepatitis (NASH) is among the leading causes of liver disease worldwide. It is increasingly recognized that the phenotype of NASH may involve a number of different pathways, of which each could become important therapeutic targets. The aim of this study is to use high resolution mass spectrometry (MS) and phosphoproteomics techniques to assess the serum proteome and hepatic phosphoproteome in subjects with NASH-related fibrosis.MethodsSixty-seven biopsy-proven NAFLD subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…[31][32][33][34][35][36] Recently, there has been interest in gut microbiome to identify signatures for advanced fibrosis in NAFLD, 37,38 as well as proteomic or multihttp://www.e-cmh.org https://doi.org/10.3350/cmh.2020.0181 omic studies. 39,40 However, these methods are all indirect measures of fibrosis encumbered by confounders and lack of specificity. Some of the most pressing issues with noninvasive tests are difficulty in determining the optimum cut-off to differentiate intermediate stages of fibrosis; inability to reflect architectural changes/fibrosis stage that may not correspond with amount of collagen deposition; and the incapability to assess the dynamic nature of fibrosis progression or regression.…”
Section: Noninvasive Tests For Fibrosis Assess-mentmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35][36] Recently, there has been interest in gut microbiome to identify signatures for advanced fibrosis in NAFLD, 37,38 as well as proteomic or multihttp://www.e-cmh.org https://doi.org/10.3350/cmh.2020.0181 omic studies. 39,40 However, these methods are all indirect measures of fibrosis encumbered by confounders and lack of specificity. Some of the most pressing issues with noninvasive tests are difficulty in determining the optimum cut-off to differentiate intermediate stages of fibrosis; inability to reflect architectural changes/fibrosis stage that may not correspond with amount of collagen deposition; and the incapability to assess the dynamic nature of fibrosis progression or regression.…”
Section: Noninvasive Tests For Fibrosis Assess-mentmentioning
confidence: 99%
“…Composite scoring systems based on serum biomarkers, such as fibrosis-4 (FIB-4) index, NAFLD fibrosis score (NFS), and enhanced liver fibrosis (ELF) test, have also been developed as surrogate measures of fibrosis severity in NAFLD [ 31 - 36 ]. Recently, there has been interest in gut microbiome to identify signatures for advanced fibrosis in NAFLD [ 37 , 38 ], as well as proteomic or multiomic studies [ 39 , 40 ]. However, these methods are all indirect measures of fibrosis encumbered by confounders and lack of specificity.…”
Section: Noninvasive Tests For Fibrosis Assessmentmentioning
confidence: 99%
“…Several studies have investigated hepatic proteome alone or in combination with blood proteome, either in animal models or in humans with NAFLD, aiming to answer fundamental pathophysiological questions [ [127] , [128] , [129] ]. In one recent study, the levels and cellular distributions of 6000 liver proteins and 16,000 phosphopeptides have been assessed in the liver of mice developing hepatic steatosis due to high fat diet (HFD).…”
Section: Proteomicsmentioning
confidence: 99%
“…In a combined hepatic phosphoproteome and serum proteome analysis of 67 biopsy-proven NAFLD subjects, the ASK1-MAPK pathway that is activated by IL-10 was recognized as important for liver fibrosis, indicated by its strong association with higher % of hepatic collagen. In serum, alpha-2 macroglobulin and coagulation factor V were strongly associated with hepatic collagen [ 127 ]. It has thus been suggested that these pathways can potentially serve as therapeutic targets.…”
Section: Proteomicsmentioning
confidence: 99%
“…It is well known that p38 MAPK participates in the regulation of inflammatory response [24]. The involvement of the apoptosis signal-regulating kinase 1 (ASK1)-MAPK pathway, the transducer activator transcription 3 and other survival pathways insulin receptor substrate 2 via phosphoinositide 3-kinase (PI3k) and its downstream effectors 3-phosphoinositide dependent protein kinase-1, ribosomal protein S6 kinase polypeptide 1 and v-protein kinase B (Akt) oncogene homolog) in NASH and NASH-related fibrosis has been also suggested [25,26].…”
Section: Introduction: Ischemia-reperfusion Mapks and Nafld Patientsmentioning
confidence: 99%